An approach to construct a three-dimensional isogeometric model from μ-CT scan data with an application to the bridge of a violin - Marschke, Sandra; Wunderlich, Linus; Ring, Wolfgang; Achterhold, Klaus; Pfeiffer, Franz (Computer Aided Geometric Design, 2020)
We present an algorithm to build a ready to use isogeometric model from scan data gained by a μ-CT scan. Based on a three-dimensional multi-patch reference geometry, which includes the major topological features, we fit the outline, then the cross-section and finally the three-dimensional geometry. The key step is to fit the outline, where a non-linear least squares problem is solved with a Gauss-Newton approach presented by Borges and Pastva (2002). We extend this approach by a regularisation and a precise interpolation of selected data points. The resulting NURBS geometry is ready for applying isogeometric analysis tools for efficient numerical simulations. As a particular example we examine the scan data of a violin bridge and present the complete workflow from the μ-CT scan up to the numerical simulation based on isogeometric mortar methods. We illustrate the relevance of the constructed geometry with a vibro-acoustical application.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Geometry construction; Isogeometric analysis; NURBS volume; Spline fitting; Vibro-acoustics; μ-CT scan data